Editorial: the livestock revolution and ICTs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Over the last decade the growing global demand for livestock products has given rise to a real ´livestock revolution´.